Enhancing English Language Learning Through Artificial Intelligence: Opportunities, Challenges and the Future - Yuli Rohmiyati (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study explores how Artificial Intelligence (AI) is being used in learning English and looks at its benefits and challenges. AI tools like chatbots, personalized learning apps, and language processing software are helping students practice English by giving quick feedback and adapting to each learner's pace. These tools improve skills in speaking, listening, and writing. However, there are still some challenges, such as AI's difficulty understanding cultural situation, limited access to AI in some areas, privacy concerns, and the risk of students relying too much on technology instead of human interactions. This study use literature research to describe AI improve English learning, opportunities and challenges in using AI. This review showed that AI can make the future of English learning, helping teachers, policymakers, and researchers understand both its potential and its limits. By using AI students has great potential to improve language, so It’s important to implement it thoughtfully to ensure it complements traditional teaching and creates an inclusive environment for all students.